SISTEM INFORMASI AKUNTANSI GADAI EFEK PADAPT PEGADAIAN (PERSERO) - Andhika Valentino Puang, - (2022)
This final report aims to find out how the procedure of the securities pawn system at PT Pegadaian (Persero) which has the specific purpose of writing this final project. The securities pawn system is one of the products offered by Pegadaian, the securities pawn system procedure has an alternative goal in asset (securities) monetization for the production and consumptive needs of the securities pawning activities as well as to encourage capital market transactions and government programs to invest in the capital market.